Pulse-labeling Studies on Protein Synthesis in Developing Pea Seeds and Evidence of a Precursor Form of Legumin Small Subunit - Spencer, Donald (1980)
Intact cotyledons were taken from pea seeds at various stages during seed development and pulse-labeled with (14)C-amino acids. Salt-soluble proteins then were extracted and fractionated on Na dodecyl sulfate-polyacrylamide gels. Storage proteins in these extracts were identified by their binding to immunoaffinity columns. The labeling studies showed that the synthesis of storage protein polypeptides accounts for a major part of total protein synthesis of developing cotyledons between 10 and 22 days after flowering. The distribution of the incorporated radioactivity between individual storage protein polypeptides varied with stage of development. For example, the synthesis of the 50 kilodalton complex of vicilin subunits dominated the early stages of protein accumulation but was a negligible proportion of the total incorporation in the later stages. On the other hand, the 75 kilodalton vicilin subunit was synthesized throughout this entire period. The major small subunit of legumin (20 kilodaltons) was not detected by either Coomassie blue staining or by 2-hour labeling during this period. It was found to arise during the desiccation phase of seed maturation from a long-lived precursor with a relative electrophoretic mobility equivalent to 19 kilodaltons.